Airy-based equilibrium mesh-free method for static limit analysis of plane problems - Le, Canh V.; Ho, Phuc L. H.; Nguyen, Hoa T. (Vietnam Journal of Mechanics, 2016)
This paper presents a numerical procedure for lower bound limit analysis of plane problems governed by von Mises yield criterion. The stress fields are calculated based on the Airy function which is approximated using the moving least squares technique. With the use of the Airy-based equilibrium mesh-free method, equilibrium equations are ensured to be automatically satisfied a priori, and the size of the resulting optimization problem is reduced significantly. Various plane strain and plane stress with arbitrary geometries and boundary conditions are examined to illustrate the performance of the proposed procedure.